Study for quality and amount of carbonic acids in the leaves of Urtica dioica L. - G. P. Smoilovska (Zaporozhye State Medical University, 2015)
Search and elaboration of plant-based drugs which stimulate physiological functions of organism are key trend of current scientific researches. Aim. The identification and analysis of organic and fatty acids amount by gas chromate-mass-spectrometry on the chromatograph Agilent Technology 6890N with mass-spectrometric detector 5973N, has been performed to assess the amount of some species of carbonic acids in the leaves of Urtica dioica. Methods and results. Components have been identified accordingly to the comparison results of mass-spectra substances separated within chromatography with the data in references for mass-spectra NIST02 and WILEY 2007. 14 Organic and 17 fatty acids have been identified. Citric acid predominated in organic acids (50.65%), palmitic (33.19%), linolenic (32.50%), linoleic (20.27%) were prevailing in fatty acids. The total amount of organic acids was 1776.6 mg/kg, fatty ones was 15731.9 mg/kg. Conclusion. The obtained results convinced that researches on raw materials from Urtica dioica as a source of natural biologic substances for manufacturing mono-and polycomponent phytodrugs are promising.